Why do next generation farmers decide to invest in Farm businesses? - Löfgren, Johan; Olsson, Sebastian (2019)
The growing world population will lead to an increased demand for food in the future. Feeding the population is considered to be the main function of agriculture. Previous literature has concluded that the share of young farmers in Sweden is too low, this is referred to as the Young farmer problem. This can partly be explained by the barriers hindering the next generation farmers from investing in farm businesses. To increase the production in the agriculture sector, young farmers need to invest in farm businesses since they are considered to be more productive and efficient than older farmers. Despite the need of young farmers, there is no previous research regarding why young farmers invest in farm businesses. We argue it is important to increase the understanding of why young farmers invest in farm businesses to emphasize the values of being a farmer and attract more young farmers to the agriculture sector.